Microbiological assessment of sachet water “pure water” from five regions in Ghana [version 2; peer review: 2 approved] - Lydia Mosi; Samuel Mawuli Adadey; Sandra Akoley Sowah; Charles Yeboah (AAS Open Research, 2019)
Background: Sachet water, popularly known as “pure water” has become an invaluable entity in most Ghanaian households. Despite its importance, there is no extensive nationwide investigations on its wholesomeness for consumption. The aim of this study was to determine the microbiological quality of 41 brands of sachet water sampled in 16 districts across 5 regions in Ghana. Methods: The samples were analyzed for the presence of total and fecal coliform (Escherichia coli) using the Colilert*- 18 Test Kit. Results: Majority of the samples (56.09%) were excellent, 4.87% satisfactory and 14.63% suspicious. Ten samples (24.4%) were unsatisfactory. For the degree of fecal contamination, (85.56%) were satisfactory, four (9.76%) were suspicious, and two others (4.88%) were unsatisfactory. The contaminations observed could be attributed to poor sanitary conditions (during and/or after production) and failure of some production facilities to adhere to standard manufacturing practices. Conclusion: Our data suggest that microbiological quality sachet water from some sources have not yet attained levels that make it absolutely pure and wholesome for consumption in many areas.